Dihydromyricetin ameliorates osteogenic differentiation of human aortic valve interstitial cells by targeting c-KIT/interleukin-6 signaling pathway - Zhang, Shaoshao; Fan, Leilei; Wang, Yongjun; Xu, Jianjun; Shen, Qiang; Xie, Jianhua; Zeng, Zhipeng; Zhou, Tingwen (Frontiers in Pharmacology, 2022)
Aims Calcific aortic valve disease (CAVD) is a chronic cardiovascular disease with high morbidity, that lacks effective pharmacotherapeutics. As a natural flavonoid extracted from Ampelopsis grossedentata, dihydromyricetin (DHM) has been shown to be effective in protecting against atherosclerosis, yet the therapeutic role of DHM in CAVD remains poorly understood. Herein, we aimed to clarify the therapeutic implications of DHM in CAVD and the underlying molecular mechanisms in human valvular interstitial cells (hVICs). Methods and Results The protein levels of two known osteogenesis-specific genes (alkaline phosphatase, ALP; runt-related transcription Factor 2, Runx2) and calcified nodule formation in hVICs were detected by western blot and Alizarin Red staining, respectively. The results showed that DHM markedly ameliorated osteogenic induction medium (OM)-induced osteogenic differentiation of hVICs, as evidenced by downregulation of ALP and Runx2 expression and decreased calcium deposition. The SwissTargetPrediction database was used to identify the potential AVC-associated direct protein target of DHM. Protein-protein interaction (PPI) analysis revealed that c-KIT, a tyrosine-protein kinase, can act as a credible protein target of DHM, as evidenced by molecular docking. Mechanistically, DHM mediated inhibition of c-KIT phosphorylation drove interleukin-6 (IL-6) downregulation in CAVD, thereby ameliorating OM-induced osteogenic differentiation of hVICs and aortic valve calcification progression. Conclusion DHM ameliorates osteogenic differentiation of hVICs by blocking the phosphorylation of c-KIT thus reducing IL-6 expression in CAVD. DHM could be a viable therapeutic supplement to impede CAVD.